Impact of the COVID-19 Pandemic on Children With Neurodevelopmental Disorders When School Closures Were Lifted - Suzuki, Kota; Hiratani, Michio (Frontiers in Pediatrics, 2021)
Human activities have been changing in conjunction with the status of the coronavirus disease 2019 (COVID-19) pandemic, with school closures and activity cancellations becoming commonplace. As such, the COVID-19 pandemic likely also has had a detrimental impact on the behavioral problems of children with neurodevelopmental disorders (NDD). In Japan, the government issued a stay-at-home order causing children to stop participating in school activities following the first declaration of a state of emergency (April 7 to May 25, 2020). During winter 2020, the stay-at-home order and school closures were lifted. Using longitudinal data of children with NDD, we compared the behavioral problems of children with NDD between October 1 and December 31, 2020 (i.e., winter 2020) with their behavioral problems before the COVID-19 pandemic (preCOVID-19). In this study, 143 caregivers of children with NDD evaluated their behavioral problems using the Japanese version of the Aberrant Behavior Checklist (ABC-J) in the preCOVID-19 period and winter 2020. We found no scores that were higher in winter 2020 compared to preCOVID-19. Moreover, irritability and hyperactivity scores were significantly lower in winter 2020 compared to preCOVID-19. These findings suggest weak negative impacts of the COVID-19 pandemic on the behavioral problems of children with NDD. In schools and clinical practice, children learned knowledge about COVID-19 and related preventive behaviors. Therefore, these practices may have alleviated the negative impact of the COVID-19 pandemic on children with NDD.